IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS CANVA UNTUK MENINGKATKAN MOTIVASI BELAJAR - Fitriana, Nur; Idawati; Mariati (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
IPAS subjects are often considered difficult due to abstract concepts that require effective visualization so that the delivery of material can run well and can increase student participation. This study aims to increase the learning motivation of grade III students at SD Negeri Sungguminas V through the implementation of Canva-based learning media. This research used the Classroom Action Research (PTK) method which was carried out in two cycles. The research subjects were third grade students with a total of 32 students in the 2024/2025 school year. The results showed that the use of Canva-based learning media can significantly increase students' learning motivation. This shows that the pre-school learning motivation of students was 54.06%, while in cycle 1 there was an increase of 61.97% and in cycle 3 it was 60.72%. There is a significant increase from each cycle. This can be seen from the increase in students' activities in participating in learning, the positive response of students to the use of Canva-based learning media, and the increase in students' learning motivation. The conclusion of this study is that Canva-based learning media can be an effective and efficient alternative or solution to increase students' learning motivation, especially in IPAS subjects.